Metagenomic Next-Generation Sequencing to Investigate Infectious Endophthalmitis of Brucella: A Case Report - Xi, Huiyu; Zhang, Lishuai; Xu, Bo; Liu, Haiyang; Li, Suyan (Frontiers in Medicine, 2022)
Introduction: Brucellosis as a systemic disease exists prevalently in clinical manifestations. The symptoms of an organ such as ocular brucellosis can lead to misdiagnosing or even undiagnosing. Metagenomic Next-generation Sequencing(mNGS), a high-throughput sequencing approach, could be applied for detecting microorganisms. Case presentation: A 57-year-old female with acute right-eye vision loss, treated with clindamycin and dexamethasone sodium phosphate lasting 1.5 months, was hard to be diagnosed with regular methods. mNGS was utilized for the aqueous fluid from the patient and Brucella melitensis were identified. With the antibiotherapy for three months, the resolution of inflammation occurred. However, even with specific medicine and surgery, the vision remained poor because severe ocular conditions last for a long time. Conclusions: It suggests that brucella should still be a probable pathogen in endophthalmitis even though the low incidence in non-epidemic areas. Moreover, mNGS can achieve early diagnosis and timely treatment for difficult-to-diagnose ocular infections.